2005
DOI: 10.1007/s00127-005-0862-9
|View full text |Cite
|
Sign up to set email alerts
|

An innovative and reliable way of measuring health-related quality of life and mental distress in the deaf community

Abstract: For deaf individuals whose preferred communication is sign language, quality of life and mental distress can be effectively and reliably assessed with the use of carefully translated and adapted common instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 7 publications
1
35
1
1
Order By: Relevance
“…General health-related quality of life (HRQoL) measures, like the Medical Outcomes Study Short Form 36 Item survey (SF-36), measure satisfaction and functioning in a number of domains, including physical, mental and social, and, often, limitations and general health [20]. The QoL results can be used as a health predictor, determinant or outcome and have been shown to be correlated with fatal and non-fatal health outcomes and health care utilization [21][22][23][24][25]. We believe measuring HRQoL in this context will help us to understand the impact of the conflict on health and, subsequently, to improve public health planning and programming.…”
Section: Introductionmentioning
confidence: 99%
“…General health-related quality of life (HRQoL) measures, like the Medical Outcomes Study Short Form 36 Item survey (SF-36), measure satisfaction and functioning in a number of domains, including physical, mental and social, and, often, limitations and general health [20]. The QoL results can be used as a health predictor, determinant or outcome and have been shown to be correlated with fatal and non-fatal health outcomes and health care utilization [21][22][23][24][25]. We believe measuring HRQoL in this context will help us to understand the impact of the conflict on health and, subsequently, to improve public health planning and programming.…”
Section: Introductionmentioning
confidence: 99%
“…Paper versions have been employed in the majority of prior studies involving the WHOQOL-BREF, although recently computer-based formats have been reported (Baumann, Ionescu, & Chau, 2011;Fellinger et al, 2005;Mason, Skevington, & Osborn, 2004;Skevington & Day, unpublished). Arguably, having two data collection formats in this study may have introduced an additional variable, however, Chen et al (2009) found no significant differences between domain scores collected either electronically or using paper and pencil.…”
Section: Discussionmentioning
confidence: 99%
“…Other examples of the new uses of the web are in collecting sensitive data (sexual behaviour diary) from a population of university women, and structured treatment programs and preventive intervention for people with mental health concerns [45,46]. A group for whom the web could potentially be an appropriate survey mode is deaf individuals [47]. Computerized administration also allows researchers to obtain sample sizes that far exceed those obtained with most traditional techniques [48].…”
Section: Data Qualitymentioning
confidence: 98%